IMPLEMENTASI KURIKULUM CAMBRIDGE DAN IMPLIKASINYA TERHADAP KEMAMPUAN BERPIKIR TINGKAT TINGGI PESERTA DIDIK - Elnar, Marlianti Rostianti; Kurnisar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the implementation of the Cambridge Curriculum in SMA Negeri 1 Palembang and its implications for students' higher-order thinking skills. This study uses quantitative methods and Ex Post Facto design. The subjects of this study were all 96 students in grades 10 and 11 of the Cambridge program. A total of 30 students were sampled using the non-probability sampling method. Data were collected through questionnaires and interviews. Analysis using one sample T-Test produced a significance level (2-Tailed) of around 0.001, which is smaller than 0.05. This shows that the implementation of the Cambridge curriculum has a significant impact on students' higher-order thinking skills, which is reflected through the curriculum framework with a wide selection of subjects and an emphasis on aspects of evaluation and higher-order thinking. In addition, this curriculum applies the principles of constructivism, where students play an active role in building knowledge and experience according to their interests in science, art, and language.